Hypertension in autosomal dominant polycystic kidney disease: a meta-analysis. Issue 12 (10th June 2016) - Marlais, Matko; Cuthell, Oliver; Langan, Dean; Dudley, Jan; Sinha, Manish D; Winyard, Paul J D
Abstract : Context: Autosomal dominant polycystic kidney disease (ADPKD) is a common disorder that can cause hypertension during childhood, but the true prevalence of hypertension during childhood is not known. Objective: We undertook a systematic review and meta-analysis to determine the prevalence of hypertension in children with ADPKD. Data sources: Systematic review of articles published between 1980 and 2015 in MEDLINE and EMBASE. Study selection: Studies selected by two authors independently if reporting data on prevalence of hypertension in children and young persons aged <21 years with a diagnosis of ADPKD. Observational series were included with study populations of >15 children. Articles were excluded if inadequate diagnostic criteria for hypertension were used. Studies with selection bias were included but analysed separately. Data extraction: Data extracted on prevalence of hypertension, proteinuria and reduced renal function using standardised form. Meta-analysis was performed to calculate weighted mean prevalence. Results: 903 articles were retrieved from our search; 14 studies met the inclusion criteria: 1 prospective randomised controlled trial; 8 prospective observational studies; and 5 retrospective cross-sectional studies. From 928 children with clinically confirmed ADPKD, 20% (95% CI 15% to 27%) were hypertensive. The estimated prevalence of proteinuria in children with ADPKD is 20% (8 studies; 95% CI 9% to 40%) while reduced renal function occurred in 8% (5 studies; 95% CI 2% to 26%). Limitations: Studies showed a high degree of methodological heterogeneity (I 2 =73.4%, τ 2 =0.3408, p<0.0001). Most studies did not use ambulatory blood pressure (BP) monitoring to diagnose hypertension. Conclusions: In this meta-analysis we estimate 20% of children with ADPKD have hypertension. In the population, many children with ADPKD are not under regular follow-up and remain undiagnosed. We recommend that all children at risk of ADPKD have regular BP measurement.